2003
DOI: 10.1093/jxb/erg021
|View full text |Cite
|
Sign up to set email alerts
|

Redox regulation and storage processes during maturation in kernels of Triticum durum

Abstract: Metabolic changes during the development and maturation of Triticum durum Desf. (L.) kernels were studied, with particular emphasis on changes in the redox state of ascorbate and glutathione, as well as in the activities of the enzymes responsible for the recycling of their oxidized forms (ascorbic free radical reductase, EC 1.6.5.4; dehydroascorbate reductase, EC 1.8.5.1; glutathione reductase, EC 1.6.4.2) and for detoxification or utilization of hydrogen peroxide (ascorbate peroxidase, EC 1.11.1.11; catalase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(85 citation statements)
references
References 40 publications
7
77
0
1
Order By: Relevance
“…12,33,44 The respective up-and downregulation of SOD and APX proteins in the rice endosperm ( Figure 8) was consistent with the expression profiles of the 2 protein types in wheat seeds, which are involved in desiccation of cereal seeds. 45,46 Aberrantly reduced expression of SOD in viviparous 1 kernels of maize led to a premature induction of endosperm PCD. 5 Our proteomic results showed that several or most of the proteins involved in diverse metabolism/cellular processes including energy metabolism and starch synthesis were coexpressed at a significantly similar level with SOD, APX, or glyoxalase I (Supplemental Table S7).…”
Section: Xu Et Almentioning
confidence: 99%
“…12,33,44 The respective up-and downregulation of SOD and APX proteins in the rice endosperm ( Figure 8) was consistent with the expression profiles of the 2 protein types in wheat seeds, which are involved in desiccation of cereal seeds. 45,46 Aberrantly reduced expression of SOD in viviparous 1 kernels of maize led to a premature induction of endosperm PCD. 5 Our proteomic results showed that several or most of the proteins involved in diverse metabolism/cellular processes including energy metabolism and starch synthesis were coexpressed at a significantly similar level with SOD, APX, or glyoxalase I (Supplemental Table S7).…”
Section: Xu Et Almentioning
confidence: 99%
“…BSO may promote transcription of these proteins by increasing the synthesis of ABA (Belmonte et al 2006), as shown by Kermode (1995). Alternatively, the BSO-induced oxidized glutathione environment may stimulate post-translational mechanisms which facilitate folding and assembling of newly synthesized storage proteins, as suggested by De Gara et al (2003). Increased accumulation of LEAs and storage products would improve the post-embryonic performance of the embryos.…”
Section: Hormone-related Mechanismsmentioning
confidence: 99%
“…Arrows represent proteins identified by mass spectrometry. decrease oxidative damage during seed development and germination (Pallanca & Smirnoff, 1999;De Gara et al, 2003) and provide antioxidant defense when acquiring desiccation tolerance (Baily et al, 2001). Among the AsA-glutathione cycle enzymes, DHAR had the highest increase in percentage during seed development (De Gara et al, 2003).…”
Section: Genotype-specific Proteinsmentioning
confidence: 99%
“…decrease oxidative damage during seed development and germination (Pallanca & Smirnoff, 1999;De Gara et al, 2003) and provide antioxidant defense when acquiring desiccation tolerance (Baily et al, 2001). Among the AsA-glutathione cycle enzymes, DHAR had the highest increase in percentage during seed development (De Gara et al, 2003). Because there is shortage of AsA in seeds (Arrigoni et al, 1992), DHAR activity during early seed germination can protect the small AsA pool from oxidation (Pallanca & Smirnoff, 1999).…”
Section: Genotype-specific Proteinsmentioning
confidence: 99%